The reception of Jane Austen in China - Sun, Shuo (2016)
In China, Jane Austen is today widely acknowledged as one of the greatest English writers. Yet her literary reputation has altered greatly since her works were first introduced to Chinese readers in the early decades of the twentieth century. This thesis will examine and explain the major changes in the Chinese reception of Austen in light of the political, social, and cultural upheavals experienced by the country over the last century. The introduction will provide a historical overview of Chinese translation and criticism of Austen’s novels. During the first half of the twentieth century, Austen was generally disapproved of by Chinese critics for restricting her writing to a limited social sphere and her fame therefore grew slowly. I will discuss the influence of Chinese political history on critical assessments regarding Austen’s conservatism and realism. Following the establishment of the People’s Republic of China in 1949, Marxism came to dominate the literary and cultural scenes. As a consequence, some Chinese translators attempted to incorporate Austen’s works into a Marxist canon, but failed. I will investigate the profound impact of the Communist Party’s political campaigns on the translation and reception of Western literature in China from the 1950s to the 1970s.